A new virus on maize in Nigeria: maize mild mottle virus - Thottappilly, G.; Qiu, W.P.; Batten, J.S.; Hughes, J.N.; Scholthof, K.B. (Scientific Societies, 1999)
Maize (Zea mays) and itch grass (Rottboellia cochinchinensis) plants exhibiting a mild mosaic or mottle were collected from a farmer's field near Mokwa, Nigeria, in 1993. Icosahedral virions (approximately 28 to 30 nm) were purified from symptomatic tissue by differential centrifugation in 0.1 M phosphate buffer, pH 7.0. The virions are composed of one single-stranded positive-sense RNA of approximately 4,000 nucleotides and, as estimated by 12.5% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), a capsid protein of approximately 28 kDa. The virus was readily detected in infected plants by enzyme-linked immunosorbent assay and immunoblot assays with a polyclonal rabbit antibody derived from purified virions. A partial cDNA library was generated with random primers. Sequence analyses of a cDNA clone representing a portion of the putative replicase gene aligned most closely with related sequences of viruses within the Tombusviridae. In particular, a region of 78 predicted amino acids surrounding the “GDD” replicase motif shares 73% identity with panicum mosaic virus and 61% identity with maize chlorotic mottle virus. The virus is readily transmitted by mechanical inoculation to sweet and dent corn, millet, and wheat. Currently it is not considered of economic importance in Nigeria. The data suggest that “maize mild mottle virus” is a newly identified virus infecting maize.